2020
DOI: 10.15252/emmm.202012102
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts: activin A adds another string to their bow

Abstract: Non‐melanoma skin cancer (NMSC) is characterized by a strong desmoplastic reaction, largely responsible for cancer aggressiveness. Within the tumour microenvironment, cancer‐associated fibroblasts (CAFs) play a key role in tumour progression, secretion of extracellular matrix proteins and recruitment of immunosuppressive cells. However, pathways involved in acquisition of CAF phenotype remain unclear. In this issue of EMBO Molecular Medicine, Cangkrama et al describe a new mechanism of fibroblast activation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…In a novel study looking at non-melanoma skin cancer (NMSC), Cangkrama et al identified cancer cell secretion of activin A, rather than TGF-β as a major activation factor for CAF cell differentiation into a protumoral phenotype through activation of a Smad2–mDia2–p53 signaling axis [ 19 , 93 ]. Their study demonstrated in PDX in vivo models and 3D organotypic models that cancer cells with high expression of activin A formed larger tumors and also had significantly higher invasion of the basement membrane layers, in addition to significantly increased stromal fibroblast proliferation rates.…”
Section: Caf Promotion Of Tumor Growth and Maintenance Of Stemnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In a novel study looking at non-melanoma skin cancer (NMSC), Cangkrama et al identified cancer cell secretion of activin A, rather than TGF-β as a major activation factor for CAF cell differentiation into a protumoral phenotype through activation of a Smad2–mDia2–p53 signaling axis [ 19 , 93 ]. Their study demonstrated in PDX in vivo models and 3D organotypic models that cancer cells with high expression of activin A formed larger tumors and also had significantly higher invasion of the basement membrane layers, in addition to significantly increased stromal fibroblast proliferation rates.…”
Section: Caf Promotion Of Tumor Growth and Maintenance Of Stemnessmentioning
confidence: 99%
“…Notably, CAFs have been identified in numerous systemic cancers in which they embody unique roles, illustrating their heterogeneity [ 9 ]. Cancers where CAFs have definitively been characterized span solid tumors and carcinomas across almost every physiologic system, including head and neck [ 8 , 10 , 11 ], breast [ 12 , 13 , 14 ], lung [ 15 , 16 , 17 , 18 ], skin [ 19 , 20 , 21 ], gastrointestinal (GI) and biliary tract [ 22 , 23 , 24 ], and genitourinary (GU) cancers [ 25 , 26 ]. To date, there has not been any indication that CAFs are implicated in lymphoid and hematopoietic cancers, and there is sparse, but growing evidence alluding to the presence of CAFs in central nervous system (CNS) cancers such as glioblastoma multiforme (GBM) [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to reprogram fibroblasts into protumorigenic CAFs via a Smad2-mediated transcriptional regulation of the formin mDia2, promoting filopodia formation and cell migration. Blockade of this paracrine activin A-mDia2 axis suppresses cancer cell malignancy and squamous carcinogenesis in vitro and in vivo [ 86 , 87 ]. As for facilitated invasiveness, keloid tissue-derived fibroblasts (KF) with upregulated LARP6 expression demonstrates enhanced cell proliferation and invasive behavior in cell culture system, while knockdown of LARP reverses this effect, with reduced deposition of type I collagen and inhibition of proliferation and invasion ability [ 88 ].…”
Section: Fibroblasts and Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Monocyte-lymphocyte ratio (MLR) is considered to be an important indicator of tumor prognosis ( Garcia et al, 2022 ). It has been reported that cancer-associated Macrophage play a key role in tumor progression, angiogenesis, invasion and recruitment of immunosuppressive cells ( Samain and Sanz-Moreno, 2020 ). Persistent immune-related gene expression and T-cell penetration were associated with clinical benefit in SKCM patients ( Shoushtari et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%